2010
DOI: 10.1162/qjec.2010.125.1.417
|View full text |Cite
|
Sign up to set email alerts
|

Was Postwar Suburbanization “White Flight”? Evidence from the Black Migration*

Abstract: Residential segregation by jurisdiction generates disparities in public services and education. The distinctive American pattern-in which blacks live in cities and whites in suburbs-was enhanced by a large black migration from the rural South. I show that whites responded to this black influx by leaving cities and rule out an indirect effect on housing prices as a sole cause. I instrument for changes in black population by using local economic conditions to predict black migration from southern states and assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
234
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(255 citation statements)
references
References 72 publications
(36 reference statements)
18
234
1
2
Order By: Relevance
“…Leah Boustan (2007) notes this problem and assesses its quantitative importance. She compares results from instruments that assign either the actual or the predicted migrant flows, where the predictions are based on push factors from source areas, and finds little difference between the two.…”
Section: [Table 6 About Here]mentioning
confidence: 99%
“…Leah Boustan (2007) notes this problem and assesses its quantitative importance. She compares results from instruments that assign either the actual or the predicted migrant flows, where the predictions are based on push factors from source areas, and finds little difference between the two.…”
Section: [Table 6 About Here]mentioning
confidence: 99%
“…This phenomenon helps to explain a pattern in which blacks live in cities and whites in suburbs: for instance, American metropolitan areas are segregated by race, both by neighborhood and across jurisdiction lines. In 1980, after a century of suburbanization, 72% of metropolitan blacks lived in central cities, compared to 33% of metropolitan whites (Boustant (2010)). The general point is that even slight homophilistic preferences can generate dramatically different outcomes compared to neutral preferences.…”
mentioning
confidence: 99%
“…In fact, natives might have responded to in-and outflows by relocating their labor or capital across states. Notably, during this period there was an important reallocation of labor: the movement of blacks from southern to northern states, 7 relocation of white natives from urban to suburban areas (Boustan, 2010), and numerous other internal responses to local labor market shocks (Ferrie, 2006). Second, Bandiera et al (2010) showed that INS immigration statistics substantially 4 CPI collected from the U. S. Department of Labor, Bureau of Labor Statistics (1984-05-11).…”
Section: Resultsmentioning
confidence: 99%